A transform program for finite element data - Che Muda, Zakaria (2008)
This paper describes the problem that a structural analyst may experience trying to cope with the particular features and peculiarities of a number of different Finite Element packages. The pre-processing program developed by the author help to alleviate many of the problems by providing an interface sub-system FINASAS whereby ASAS F.E package can be assessed via the the FINELE input system.